2019
DOI: 10.1177/2633366x19896584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reinforcement and processing on aluminum matrix composites modified by stir casting route

Abstract: In the present study, the individual and combined effect of reinforcement on aluminum (Al; 6063) alloy is discussed. These Al metal matrix composites with individual and multiple reinforcements are finding increased application in aerospace, automobile industry, underwater machines, and transportation application, due to improved mechanical and tribological properties like strong, stiff, wear, and impact resistance. Al 6063 alloy reinforced with different elements such as two types of ceramic mortar ash (MA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Results obtained showed remarkable reduction in wear rate as well as improvement in hardness and tensile strength properties. Other forms of agro wastes for AMCs have also been documented (Arora & Sharma, 2018;Donald et al, 2018;Krushna, Shekhar, & Kumar, 2019;Rozhbiany & Jalal, 2019;Yekinni et al, 2019).…”
Section: Agro-waste-based Ceramic Reinforcementsmentioning
confidence: 88%
“…Results obtained showed remarkable reduction in wear rate as well as improvement in hardness and tensile strength properties. Other forms of agro wastes for AMCs have also been documented (Arora & Sharma, 2018;Donald et al, 2018;Krushna, Shekhar, & Kumar, 2019;Rozhbiany & Jalal, 2019;Yekinni et al, 2019).…”
Section: Agro-waste-based Ceramic Reinforcementsmentioning
confidence: 88%
“…Other researchers used straw ash (agricultural waste, 5 wt %) and met coke ash (industrial waste, 5 wt %) as waste fillers in hybrid composites [ 60 ]. Additional studied non-waste fillers were mortar ash (5 wt %) and nanofibrillated composite (5 wt %).…”
Section: Agricultural Waste Materialsmentioning
confidence: 99%
“…For that reason, the studies on surface strengthening of graphene oxide added AMC have been carried out by using techniques such as stirred casting, liquid metal impregnation, sprayed deposition casting and so on (Toptan et al, 2010;Fadavi Boostani et al, 2018;Wu et al, 2019;Zheng et al, 2020a;Pehlivanlı & Pul, 2021). However, no study has been found on the graphene oxide-added AMCs with stirred casting so far using surface hardening processes like shot peening (Sun et al, 2018;Zhu et al, 2019;Rozhbiany & Jalal, 2019;Sasikumar et al, 2020) With the shot peening process, the surface of the graphene oxide structured AMC will be hardened by a massive amount of high hardness and high-speed kinetic energy projectiles (Zhu et al, 2016;Zhan et al, 2018a;Zhan et al, 2018b). After shot peening, residual stress field and microstructure enhance its fatigue, surface hardness, resistance to stress corrosion cracks or high temperature oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%